2013
DOI: 10.1073/pnas.1221306110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of naïve lung CD4 T cells provides evidence of functional lung to lymph node migration

Abstract: The proportion of CD4 T cells with phenotypic and functional properties of naïve cells out of total CD4 T cells is similar in the lung parenchyma and lymph nodes. On treatment with a sphingosine-1-phosphate agonist, the frequency of these cells falls precipitously, but with a delay of ∼14 h compared with blood CD4 T cells; neither anti-CD62L nor pertussis toxin prevents entry of naïve CD4 T cells into the lung. Based on treatment with anti-CD62L and the use of CCR7 −/− cells, lung naïve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 47 publications
0
31
1
1
Order By: Relevance
“…How PT might reduce expression of these adhesion markers is not clear, but one study found that IL-6 reduced L-selectin levels on neutrophils in rabbits (Suwa et al 2002), and increased IL-6 has been associated with pertussis and with PT activity Andreasen, Powell and Carbonetti 2009;Richard et al 2011). In contrast, extravasation of T cells into non-lymphoid tissue is not inhibited by PT treatment (Cose et al 2006;Caucheteux, Torabi-Parizi and Paul 2013).…”
Section: Mechanisms Causing Leukocytosis In Pertussismentioning
confidence: 99%
“…How PT might reduce expression of these adhesion markers is not clear, but one study found that IL-6 reduced L-selectin levels on neutrophils in rabbits (Suwa et al 2002), and increased IL-6 has been associated with pertussis and with PT activity Andreasen, Powell and Carbonetti 2009;Richard et al 2011). In contrast, extravasation of T cells into non-lymphoid tissue is not inhibited by PT treatment (Cose et al 2006;Caucheteux, Torabi-Parizi and Paul 2013).…”
Section: Mechanisms Causing Leukocytosis In Pertussismentioning
confidence: 99%
“…These receptors are generally believed to promote localization of naïve CD4 T cells to central and regional antigen surveil-lance via continual trafficking through the secondary lymphoid organs (SLOs) via the blood, though a recent study has questioned the functional necessity for CCR7. 2931 This trafficking pattern targets T cells to the paracortical regions of lymph nodes and the parafollicular regions of the spleen, where they scan antigen-presenting cells (APCs), particularly dendritic cells, for cognate antigens. 32 Importantly, naïve T cells in mice lack expression of the murine activation marker CD44, while human naïve T cells bear the naïveté-associated surface marker CD45RA but not the activation markers CD45RO or CD69.…”
Section: Early Cd4 T-cell Memory Developmentmentioning
confidence: 99%
“…Studies on migration of radioactively labeled neutrophils in several mammalian species suggest that the majority of neutrophils are retained during passage via the lung [61][63]. A recent study also suggested that naive CD4 T lymphocytes are retained in the lung for substantial periods of time [64]. Overall, previous studies indicate that under normal, uninflammatory conditions lymphocytes may spend substantial amount of time while traveling via the capillary bed of the lung.…”
Section: Introductionmentioning
confidence: 98%